2021
DOI: 10.1080/14737167.2021.1878880
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analyses comparing cemented, cementless, hybrid and reverse hybrid fixation in total hip arthroplasty: a systematic overview and critical appraisal of the current evidence

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(183 reference statements)
0
4
0
1
Order By: Relevance
“…4 Because of issues in their methodology and reporting, this study was excluded from the in-depth analyses on cost-effectiveness in our review. 2 However, in this paper, it was reported that early revision was higher in cementless fixation than cemented fixation (1.6% versus 1.4%), without any difference in QALYs. The costs were higher in cementless fixation compared with cemented fixation (€6,734 vs. €3,155).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…4 Because of issues in their methodology and reporting, this study was excluded from the in-depth analyses on cost-effectiveness in our review. 2 However, in this paper, it was reported that early revision was higher in cementless fixation than cemented fixation (1.6% versus 1.4%), without any difference in QALYs. The costs were higher in cementless fixation compared with cemented fixation (€6,734 vs. €3,155).…”
mentioning
confidence: 67%
“…We share the same enthusiasm for CEAs in THA as the authors, which led to our recently published review on the cost-effectiveness of different implant fixation modes in THA in particular. 2 Nevertheless, since our findings are not in accordance with the statements presented in the paper of Agarwal et al, we aimed to write this letter with a critical note.…”
mentioning
confidence: 70%
“…It is extensively described that cementless fixation in very elderly subjects could lead to more implant-related complications compared to cemented fixation and is therefore not recommended in this age group. 1 , 2 , 7 , 8 , 37 As a consequence, a substantial part of the elderly patients will be treated with a cemented stem in daily practice. Therefore, there is a high probability that especially elderly patients with an obvious wide femoral canal and thin cortices did not receive the studied cementless stem.…”
Section: Discussionmentioning
confidence: 99%
“…Ein umfassender Review aktueller Studien zur Kosteneffizienz unterschiedlicher Fixationsmethoden zeigt, dass eine zementierte oder hybride Verankerung die kosteneffizienteste Wahl ist. Ausschließlich in der sehr jungen Patientengruppe (unter 43 Jahren) stellte ein zementfreies Hüftschaftimplantat die kostengünstigste Option dar [ 58 ].…”
Section: Kosteneffiziente Versorgungunclassified